Comparison of the effect of propolis and Gluma desensitizer on the management of dentin hypersensitivity: a randomized controlled trial - Marina Shah; Shahbaz Ahmed Jat; Munazza Aziz (Journal of the Pakistan Medical Association)
Objective: To compare the effect of propolis and gluma desensitisers on the management of dentin hypersensitivity.